Proteomic and Metabolomic Characterization of Human Neurovascular Unit Cells in Response to Methamphetamine. Issue 9 (3rd August 2020) - Herland, Anna; Maoz, Ben M.; FitzGerald, Edward A.; Grevesse, Thomas; Vidoudez, Charles; Sheehy, Sean P.; Budnik, Nikita; Dauth, Stephanie; Mannix, Robert; Budnik, Bogdan; Parker, Kevin Kit; Ingber, Donald E.
Abstract: The functional state of the neurovascular unit (NVU), composed of the blood–brain barrier and the perivasculature that forms a dynamic interface between the blood and the central nervous system (CNS), plays a central role in the control of brain homeostasis and is strongly affected by CNS drugs. Human primary brain microvascular endothelium, astrocyte, pericyte, and neural cell cultures are often used to study NVU barrier functions as well as drug transport and efficacy; however, the proteomic and metabolomic responses of these different cell types are not well characterized. Culturing each cell type separately, using deep coverage proteomic analysis and characterization of the secreted metabolome, as well as measurements of mitochondrial activity, the responses of these cells under baseline conditions and when exposed to the NVU‐impairing stimulant methamphetamine (Meth) are analyzed. These studies define the previously unknown metabolic and proteomic profiles of human brain pericytes and lead to improved characterization of the phenotype of each of the NVU cell types as well as cell‐specific metabolic and proteomic responses to Meth. Abstract : Although primary human neurovascular unit (NVU) cells are widely used in CNS research, they are poorly characterized, In this work, a deep coverage proteome, secreted metabolome, and respiratory functions of the main four cell types in the human NVU, in both normal conditions and stimulated with the neuropsychiatric drug—methamphetamine, are presented.